Program SiMantep Analisis Konsep Takaful dan Theory of Planned Behavior: Studi Kabupaten Bengkalis - Muhamad Aji Purwanto (Kodifikasia, 2025)
Takaful as an insurance concept that emphasizes the principle of mutual assistance (ta'awun) and sharing risks (tabarru') to other insurance participants provides relief in its concept. This concept demands social solidarity and togetherness which (indirectly) aligns with sharia values. In the SiMantep program, there is also a concept of mutual assistance which can be said to be in accordance with the provisions. This study uses a qualitative method in the form of library research with secondary data sources and data collection models from government data on the SiMantep insurance program, journals and data that have been presented specifically for the Bengkalis Regency area. The data analysis method uses Miles and Hubberman: Data collection, data display, and drawing conclusions. In general, the SiMantep program targets small-scale fishermen and traditional fishermen with a high risk of work accidents, but are vulnerable to work safety guarantees. Basically, the principles applied in SiMantep are in accordance with the main principles in the takaful concept such as mutual assistance and mutual support in the management and distribution process, so that this intersection becomes an interesting concept elaboration and makes the SiMantep program in accordance with several aspects of sharia, and for the implementation of the SiMantep program based on the theory of planned behavior, the government must be more proactive in approaching fishermen.